Penyelesaian Sengketa Merek Di Indonesia Berdasarkan Undang-Undang Nomor 15 Tahun 2001 Tentang Merek - Wishnu Kurniawan; Johan Johan (Fakultas Hukum, Universitas Internasional Batam, 2015)
Today technology is a fundamental requirement for the man. There is no one who can deny the technological needs for human life today. Discovery after discovery conducted to support the development of technology. One way to protect the interests of the findings is the recognition of intellectual property rights. Disputes related to the brand chosen by the author as a brand is something that is always found in everyday life. Indonesia is a country that registered many brands, so the potential for trademark disputes in Indonesia in the future is also quite large.Methodology used in this research is the normative legal research. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and conclude, then described descriptively.Results of this study examines the decision of the brand with the legal protection dispute case number : 86/Pdt.Sus-Merek/2013/PN.NIAGA.JKT.PST with Plaintiff TCF Co. LLC, a company under the Act the State of California, USA based in 26901 Malibu Hill Road , CalabasasHills, California 91301 USA and Defendant are Stores Cheese Cake Factory in Indonesia. In this case the authors concluded that the existing brands in Indonesia are protected by Indonesian law if the trademark was registered pursuant to Act No. 15 of 2001 on Marks